An experimental investigation on the pool boiling of multi-orientated hierarchical structured surfaces. (January 2021) - Xie, Shangzhen; Jiang, Mengnan; Kong, Haojie; Tong, Qing; Zhao, Jiyun
Highlights: Experiments were carried out to decouple the contributions of the intrinsic surface wettability from the hierarchical (dual-layer) structure on the pool boiling enhancement for the horizontal surface. The nanostructured surfaces show better boiling performance than the plain surface with all multi-orientations. The departure time and the thickness of the fully developed vapor film of the inclined surfaces increase with increasing surface orientation. New correlations regarding the downward-facing CHF prediction based on the horizontal CHF are proposed. Abstract: With the increasing power consumption in the worldwide energy-intensive sectors, a more efficient thermal heat transfer during the boiling process is pressingly needed. The fundamental understanding of the boiling mechanism is essential for the enhanced heat transfer and subsequently the improvement of heat utilization. The present study decouples the contributions of the intrinsic surface wettability from the hierarchical (dual-layer) structure on the boiling enhancement by growing nanograss as the substructure and the micro flowers with different cover density as the superstructure. The structured surfaces show maximum critical heat flux (CHF) enhancement by 68%. While for the multi-orientated (from 0° to 180°) substrates, the surface orientation will influence the boiling performance through different physical mechanisms. It discloses that the departure time and the thickness of the fully developed vapor film of the inclined surfaces increase with increasing surface orientation, resulting in impeded boiling performance of the downward-facing surface. Moreover, enhanced critical heat flux and heat transfer coefficient can be observed for the nanograss surface with the downward-facing orientations. In addition, new correlations regarding the downward-facing CHF prediction based on the horizontal CHF are proposed for the future multi-oriented surface design in advanced heat-transfer applications.